2010
DOI: 10.1590/s0037-86822010000500003
|View full text |Cite
|
Sign up to set email alerts
|

Sand fly captures with Disney traps in area of occurrence of Leishmania (Leishmania) amazonensis in the state of Mato Grosso do Sul, mid-western Brazil

Abstract: INTRODUCTION: The work was conducted to study phlebotomine fauna (Diptera: Psychodidae) and aspects of American cutaneous leishmaniasis transmission in a forested area where Leishmania (Leishmania) amazonensis occurs, situated in the municipality of Bela Vista, State of Mato Grosso do Sul, Brazil. METHODS: The captures were conducted with modified Disney traps, using hamster (Mesocricetus auratus) as bait, from May 2004 to January 2006. RESULTS: Ten species of phlebotomine sandflies were captured: Brumptomyia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
0
21
0
3
Order By: Relevance
“…antunesi, the latter presenting a highly anthropophilic behavior (Andrade Filho et al 2001) and they were found naturally infected by flagellates in the State of Pará (Ryan et al 1984;Silveira et al 2002). Bichromomyia flaviscutellata, a species involved in the transmission of Leishmania (Leishmania) amazonensis in several regions of Brazil, including Mato Grosso do Sul Dorval et al 2010), was also captured. During the two years of the study, the seasonal distribution of Ny.…”
Section: Resultsmentioning
confidence: 99%
“…antunesi, the latter presenting a highly anthropophilic behavior (Andrade Filho et al 2001) and they were found naturally infected by flagellates in the State of Pará (Ryan et al 1984;Silveira et al 2002). Bichromomyia flaviscutellata, a species involved in the transmission of Leishmania (Leishmania) amazonensis in several regions of Brazil, including Mato Grosso do Sul Dorval et al 2010), was also captured. During the two years of the study, the seasonal distribution of Ny.…”
Section: Resultsmentioning
confidence: 99%
“…Clear expansion of leishmaniosis by L. (L.) amazonensis around the country has been observed over the last decades; according to Câmara-Coelho et al (2011) 8% of American cutaneous leishmaniosis cases in Brazil are caused by the above species. Several recent scientific studies describe this expansion; in terms of hosts, Souza et al (2005), Dorval et al, (2010) and Cardoso et al (2015) reported Felis catus domesticus (domestic cat), Mesocricetus auratus (hamster) and Necromys lasiurus (wild rodent) infection. In terms of geographical distribution, Dorval et al (2006), Marlow et al (2013) and Carvalho et al (2013) reported its detection in Mato Grosso do Sul, Santa Catarina and Rio de Janeiro states, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, studies on the phlebotomine fauna have been carried out in countries bordering the state of Mato Grosso do Sul [1,2]. The growth in number of vectors, humans and dogs infected in the State leads to the development of studies in the cities in order to observe the epidemiological pattern of the disease [3-5].…”
Section: Introductionmentioning
confidence: 99%